2007
DOI: 10.1007/s10014-007-0223-3
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence-guided resection of metastatic brain tumors using a 5-aminolevulinic acid-induced protoporphyrin IX: pathological study

Abstract: We performed a pathological study to identify the locus of production of protoporphyrin IX (PPIX) in human metastatic brain tumors. Patients with metastatic brain tumors (n = 11) received 1 g of 5-aminolevulinic acid (5-ALA) perorally 2 h before undergoing surgery. The target region was exposed to laser light with a peak wavelength of 405 +/- 1 nm and an output of 40 mW. Tissue samples from the tumor bulk and surrounding areas were examined by histological and fluorescence methods. Of the 11 tumors, 9 manifest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
0
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(71 citation statements)
references
References 15 publications
6
59
0
6
Order By: Relevance
“…20 In a series of 11 metastatic brain tumors, Utsuki et al reported 5-ALA positivity for 82% of metastases. 41 Also in our series, the rate of 5-ALA fluorescence positivity in metastases from breast cancer was high (71%, n = 5/7). 5-ALA fluorescence was positive in only 1 of 4 urothelial carcinoma metastases.…”
Section: -Ala Fluorescence In Brain Metastasessupporting
confidence: 52%
See 1 more Smart Citation
“…20 In a series of 11 metastatic brain tumors, Utsuki et al reported 5-ALA positivity for 82% of metastases. 41 Also in our series, the rate of 5-ALA fluorescence positivity in metastases from breast cancer was high (71%, n = 5/7). 5-ALA fluorescence was positive in only 1 of 4 urothelial carcinoma metastases.…”
Section: -Ala Fluorescence In Brain Metastasessupporting
confidence: 52%
“…Others have reported positive 5-ALA fluorescence in peri-tumor areas surrounding brain metastases. 20,36,41 These reports and our own findings indicate that more studies are needed to elucidate the potential role of 5-ALA in improving resection margins in various entities of brain metastasis. We used 5-ALA fluorescence as an immediate intraoperative indicator of tumor tissue in patients undergoing diagnostic biopsy.…”
Section: Clinical Value Of 5-ala-guided Resection Of Primary Brain Tumentioning
confidence: 64%
“…This PPIX may be found in surrounding tissues where no tumor cells exist [7]. This phenomenon is thought to be due to PPIX produced in tumor cells leaking out of the cells [8]. Also, more highly-concentrated porphyrin, particularly coproporphyrin, is reportedly excreted in the urine of brain tumor patients than by volunteers without brain tumors given 5-ALA, since porphyrins including PPIX leak out of tumor cells [5].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, ALA-PDD is officially approved as a standard procedure of diagnostics by fluorescence navigation in brain tumors 7 and bladder cancer 8 . ALA is an endogenous natural amino acid and a common precursor of chlorophyll in plants and bilirubin in animals.…”
Section: Discussionmentioning
confidence: 99%
“…Despite recent advances in surgical methods, such as laparoscopic radical prostatectomy (LRP) and robotic-assisted radical prostatectomy (RARP), there has not been enough of an improvement in the rate of positive surgical margin (PSM) in radical prostatectomy. [4][5][6] Photodynamic diagnosis (PDD) using 5-aminolevulinic acid (ALA; ALA-PDD) is clinically recognized as an effective procedure of the detection for various cancers, such as brain tumor 7 and bladder cancer. 8 Fluorescence navigation by PDD provides good visualization and detection of PSM during surgery, leads to improved surgical curability and subsequent prognosis in these cancers.…”
Section: Introductionmentioning
confidence: 99%